The middle class in world society negotiations, diversities and lived experiences - Suter, Christian 1956-; Madheswaran, S.; Vani, B. P. (Routledge, 2020)
"This volume delves into the study of the world's emerging middle class. With essays on Europe, USA, Africa, Latin America, and Asia, the book studies recent trends and developments in middle class evolution at the global, regional, national, and local levels. It reconsiders the conceptualization of middle class, with a focus on the diversity of middle class formation in different regions and zones of world society. It also explores middle class lifestyles and everyday experiences, including experiences of social mobility, feelings of insecurity and anxiety, and even middle class engagement with social activism. Drawing on extensive fieldwork and in-depth interviews, the book provides a sophisticated analysis of this new and rapidly expanding socio-economic group and puts forth some provocative ideas for intellectual and policy debates. It will be of importance to students and researchers of sociology, economics, development studies, political studies, Latin American studies, and Asian Studies"--